Coastal ecology of Pahang water (South China Sea) - Mansor, Nur Nazifah; Mustapa, Mohd Zaini (IIUM Press, 2017)
This first book of Department of Marine Science marks the combination effort and sincere support of all academic staff under the Department which has just embark its journey as one of the important Department under the umbrella of Kulliyyah of Science. The book also features some interest of the marine academic staff if not all that have been carried out to reveal the secret of marine life towards sustainable management of the marine ecosystem. This book presented research discussed on research related to the diversity of marine organism including zooplankton, benthic dinoflagellates, antibiotic resistance and distribution of phytoplankton of coastal water. The fundamental research presented in the book will surely add into existing knowledge particularly for Malaysian marine waters.